2023
DOI: 10.3390/polym15092092
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement of Injectable Hydrogel for Meniscus Tissue Engineering by Using Cellulose Nanofiber from Cassava Pulp

Abstract: Injectable hydrogels can be applied to treat damaged meniscus in minimally invasive conditions. Generally, injectable hydrogels can be prepared from various polymers such as polycaprolactone (PCL) and poly (N-isopropylacrylamide) (PNIPAAm). Poly (ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) block copolymer-diacrylate (PEO-PPO-PEO-DA) is an interesting polymer due to its biodegradability and can be prepared as water-insoluble injectable hydrogel after curing with UV light at low intensity. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Recently the facile and versatile photopolymerizing natural and synthetic polymers are on the rise in the field of tissue engineering due to their ease of applicability for fabrication of 3D architecture and inherent mechanical stability while being biologically active and compatible [254]. Jeencham et al demonstrated the use of an injectable hydrogel composed of cellulose nanofibers, gelatin methacrylate (gelMA) and PEO-PPO-PEO-DA for meniscus tissue engineering applications [255]. Chen et al integrated synovial aptamers within gelMA for the recruitment of endogenous cells for the repair of avascular meniscus lesions [256].…”
Section: Cells Materials and Growth Factors For Meniscal Tissue Engin...mentioning
confidence: 99%
“…Recently the facile and versatile photopolymerizing natural and synthetic polymers are on the rise in the field of tissue engineering due to their ease of applicability for fabrication of 3D architecture and inherent mechanical stability while being biologically active and compatible [254]. Jeencham et al demonstrated the use of an injectable hydrogel composed of cellulose nanofibers, gelatin methacrylate (gelMA) and PEO-PPO-PEO-DA for meniscus tissue engineering applications [255]. Chen et al integrated synovial aptamers within gelMA for the recruitment of endogenous cells for the repair of avascular meniscus lesions [256].…”
Section: Cells Materials and Growth Factors For Meniscal Tissue Engin...mentioning
confidence: 99%
“…Hydrogels composed of natural biomaterials have similar advantages as natural ECMs because the materials are extracted from plants or animals, which possess biocompatibility, biodegradability, and bioactivity, making them suitable for biomedical applications [46]. Commonly used natural materials and their derivatives include proteins (Figure 2; Table 1): collagen type I (COL I) [40,[47][48][49][50], gelatin (Gel) [24,51,52] and gelatin methacrylate (GelMA) [42,43,[53][54][55], fibrinogen (FB) [38,[56][57][58][59]; silk fibroin (SF) [41], polysaccharides (Figure 2; Table 1) such as hyaluronic acid (HA) [47,50] and tyramine-modified hyaluronic acid (TA-HA) [60], alginate (Alg) [61][62][63][64] and alginate dialdehyde (ADA) [51], agarose (Ag) [42,43,65], cellulose [55,61,66], chondroitin sulfate (CS) [67], and chitosan (Chi) [37,68]. Additionally, the utilization of native meniscus extracts (Figure 2; Table 1), also referred to as menisc...…”
Section: Natural Materialsmentioning
confidence: 99%
“…These characteristics make it an ideal material for use as a support structure in hydrogel systems. The incorporation of cellulose nanofibers has substantially improved the mechanical properties of injectable hydrogels, offering great potential for applications in MTE [55,66] considering the vital importance of mechanical strength in meniscus scaffolds.…”
Section: Cellulosementioning
confidence: 99%
See 2 more Smart Citations